Implementation of engineering techniques for reducing waste in Warehousing: A case study in a Peruvian Food Company - Chumpitaz-Martínez, Enzo (2022)
ompanies belonging to the food sector are exposed to a problem related to the loss of products during the production and commercialization processes, which mainly causes an increase in the amount of waste generated. The objective of this research is the reduction of waste generated during warehouse operations in a food company, which presents an increase in its waste ratio equivalent to 233% compared to previous years. The implementation of Lean Warehousing tools was developed, specifically Kaizen Teian and Kanban Pull, together with the Slotting warehouse strategy considering the useful life of the products as a criterion. With the development of these tools, the food waste ratio is expected to be reduced to a value close to the industry standard, corresponding to 0.25%.